1997
DOI: 10.1046/j.1365-2036.1997.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful low‐dose amoxycillin, metronidazole and omeprazole combination therapy in a population with a high frequency of metronidazole‐resistant Helicobacter pylori

Abstract: Aim: Effective anti‐Helicobacter pylori therapies with few side‐effects are needed. We studied the effectiveness of a low‐dose combination of metronidazole, amoxycillin and omeprazole for treatment of ulcer patients in Seoul, Korea. Methods: Patients with gastric or duodenal ulcer received metronidazole (125 mg b.d.), amoxycillin (500 mg b.d.) and omeprazole (20 mg at bedtime) for 2 weeks. Endoscopic examinations were performed before treatment and at least 6 weeks after completion of antimicrobial therapy. H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…31 The absence of recurrence after successful therapy is in accordance with a previous study in Korea. 32 When high-level disinfection of endoscopes is carried out, reinfection rate in Korea is similar to that experienced in the United States or Europe.…”
Section: Discussionmentioning
confidence: 85%
“…31 The absence of recurrence after successful therapy is in accordance with a previous study in Korea. 32 When high-level disinfection of endoscopes is carried out, reinfection rate in Korea is similar to that experienced in the United States or Europe.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, other studies have shown only a minor or no effect of metronidazole resistance in OAM 23 , . 24 …”
Section: Discussionmentioning
confidence: 99%
“…Reduced effectiveness in smokers has earlier been reported for proton pump inhibitors in the treatment of reflux oesophagitis 34 and of duodenal ulcers irrespective of antibiotic co‐treatment to eradicate Helicobacter pylori. 35 –37 The reason why proton pump inhibitors are less effective in smokers has not yet been elucidated and deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%